Tingkat Partisipasi Angkatan Kerja Perempuan Di Kabupaten Rokan Hilir (2010-2021) - Neng Murialti; M. Fikri Hadi; Mizan Asnawi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2022)
This study aims to see how the influence of GRDP, UMK, the number of women with a high school education equivalent, the number of women with diploma education and above and the number of female population aged 15-64 years on the participation rate of the female workforce in Rokan Hilir Regency for the years (2010-20210). The results of this study indicate that the variables GRDP, UMK, women with high school education equivalent, women with diploma education and above have a positive and significant effect on the level of participation of the female workforce in Rokan Hilir Regency in 2010-2021, while the variable number of female residents is negatively and not significant. on the participation rate of the female workforce in Rokan Hilir Regency.